Sacral Stress Fracture following the Bone Union of Lumbar Spondylolysis - Tatsuro Sasaji; Hideki Imaizumi; Hiroyuki Takano; Hideo Saitoh; Taishi Murakami; Ryuichi Kanabuchi; Motohiko Sekiya (Case Reports in Medicine)
While 22 articles have reported on sacral stress fractures, it is a rare injury and its etiology is not well known. We present the case of a 16-year-old male who presented with low back pain in 2015. He was a high school soccer player with a previous history of a bilateral L5 lumbar spondylolysis in 2014. The patient refrained from soccer and wore a brace for six months. Two months after restarting soccer, he again complained of low back pain. After 1 year, a lumbar spine computed tomography revealed the bone union of the spondylolysis. At his first visit to our hospital, his general and neurological conditions were normal and laboratory data were within the normal range. Sacral coronal magnetic resonance imaging (MRI) of the left sacral ala revealed an oblique lineal signal void surrounding bone marrow edema. Based on his symptoms, sports history, and MRI, he was diagnosed with a sacral stress fracture. He again refrained from soccer; his low back pain soon improved, and, after 1 year, the abnormal signal change had disappeared on sacral MRI. Recurrent low back pain case caused by a sacral stress fracture occurring after the bone union of lumbar spondylolysis is uncommon.